DP camp – literary accounts of the life “in between” An invitation to the topic - Krupa, Bartłomiej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article constitutes a preliminary attempt at reading from literature the condition of the survivors – people interned in German displaced persons’ camps immediately after WWII. In that context, the author considers the saturated with satire, grotesque, and sarcasm novel by Tadeusz Nowakowski entitled Obóz Wszystkich Świętych. Nowakowski’s vision is supplemented with Tadeusz Borowski’s story entitled Bitwa pod Grunwaldem, as well as his poems, e.g. Dary demokratyczne, and Jerzy Podgórski’s reports in the series W południowych Niemczech, in which DP camps were compared to an etching by Henry Moore presenting human-like figures sleeping in a tunnel. A separate consideration was applied to the fortunes of Ida Fink, interned in the Ettlingen camp. The writer reminisced on the time in her novel entitled The Journey, and in interviews. The analyses of the texts led the author to the conclusion that the discussed narratives indicate the inability to experience solace during (apparent) acquittal, and the inability to return to pre-WWII times.